Federico Lanzaco Salafranca, la pasión por Japón - Barlés Báguena, Elena (Mirai. Estudios Japoneses, 2025)
Federico Lanzaco Salafranca (Barcelona, 1929 – Madrid, 2025) was a Professor and Chartered Business Manager from the Barcelona School of Commerce. He held a bachelor’s degree in philosophy from the University of Comillas, a Bachelor’s degree in Theology from Loyola University (Chicago), and a Master’s degree in Linguistics from the University of Michigan (Ann Arbor). He furthered his studies at the Jesuit Centre for Japanese Studies in Tokyo and in various Linguistics, Japanese Language, and Oriental Cultures departments at several European and North American universities. During the more than nine years he lived in Japan, he devoted himself fully to its study and research and worked as a professor at Sophia University in Tokyo. After this intensive experience, he returned to Spain and entered the business world, working for over thirty years at the Spanish-Japanese company Acerinox, where he served as Deputy to the President. Throughout this period and until his retirement, he maintained an intense dedication to the study and dissemination of Japanese culture. His works are true bibliographic treasures in the field of studies on Japanese thought, religion, aesthetics and spirituality. A passionate and enthusiastic man, he was one of Spain’s most important Japanologists.